2016
DOI: 10.3945/jn.114.208520
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Analytic Method for Sulfur Compounds in Aged Garlic Extract with the Use of a Postcolumn High Performance Liquid Chromatography Method with Sulfur-Specific Detection

Abstract: We developed a rapid postcolumn HPLC method for both qualitative and quantitative analyses of sulfur compounds, and this method helped elucidate a potential mechanism of cis-S1PC and SAMC action in AGE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(73 citation statements)
references
References 19 publications
1
72
0
Order By: Relevance
“…Lawson et al showed the existence of cis-GS1PC in garlic, and its content was 0.28-0.55 µmol/g (fresh weight) [1,4]. We also confirmed the existence of cis-GS1PC in raw garlic and found that its content was 0.54 ± 0.12 µmol/g (dry-garlic) [3]. The qualitative analysis of cis-GS1PC in AGE was performed by LC-MS, and we obtained the following mass spectrum of cis-GS1PC: authentic cis-GS1PC: [M + H] + = m/z 291.1001, cis-GS1PC in AGE: [M + H] + = m/z 291.1002 (l " Fig.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…Lawson et al showed the existence of cis-GS1PC in garlic, and its content was 0.28-0.55 µmol/g (fresh weight) [1,4]. We also confirmed the existence of cis-GS1PC in raw garlic and found that its content was 0.54 ± 0.12 µmol/g (dry-garlic) [3]. The qualitative analysis of cis-GS1PC in AGE was performed by LC-MS, and we obtained the following mass spectrum of cis-GS1PC: authentic cis-GS1PC: [M + H] + = m/z 291.1001, cis-GS1PC in AGE: [M + H] + = m/z 291.1002 (l " Fig.…”
Section: Resultssupporting
confidence: 78%
“…Recently, we have reported that cis-S1PC is included in AGE [3]. The content of cis-GS1PC, a plausible precursor of cis-S1PC, in raw garlic was less than 50 % of cis-S1PC content in AGE on a molar basis [3,4]. These differences suggested that cis-S1PC was produced not only from the precursor, γ-glutamyl peptide, but also from the other compounds.…”
Section: Lc-msmentioning
confidence: 94%
See 2 more Smart Citations
“…Brie y, raw garlic (Allium sativum L.) was sliced into pieces, which was followed by immersing in ethanol 20-50% (v/v) and aging for more than 10 months at room temperature. S1PC, SAC and SAMC were synthesized according to the previous methods [41,42], and the purity was >99.0%.…”
Section: Methodsmentioning
confidence: 99%